Evaluating The Impact of Ultraviolet Radiation On Human Health: A MOORA-Based Multi-Criteria Decision Analysis - Devipriya Mani (Journal on Applied and Chemical Physics, 2026)
Ultraviolet (UV) radiation has played an important role in shaping human evolution, skin pigmentation, and health outcomes across different geographical regions. The present comparative assessment considers North America, Europe, Africa, Australia, and Asia based on skin cancer incidence, vitamin D deficiency, and psoriasis treatment outcomes. The findings indicate that Australia ranks highest overall, reflecting its substantial UV exposure and associated health considerations, particularly the greater burden of UV-related skin cancer. Africa ranks lowest, consistent with the protective role of higher melanin pigmentation against UV-induced skin damage, although vitamin D status and other health factors remain important. North America, Europe, and Asia occupy intermediate positions, reflecting differences in latitude, environmental exposure, pigmentation, lifestyle, and healthcare practices. These regional variations demonstrate the dual nature of UV radiation: moderate exposure supports vitamin D synthesis, whereas excessive exposure can cause cellular damage and increase disease risk. Overall, the comparison highlights the importance of region-specific UV protection, vitamin D management, and healthcare strategies